Analytical method for calculation of the potential profiles of nitride-based resonance tunneling structures - Boyko, I.V. (Condensed Matter Physics, 2018)
Using the effective mass model for an electron and the dielectric continuum model, analytical solutions of the self-consistent Schrödinger-Poisson system of equations are obtained. Quantum mechanical theory of electronic stationary states, the oscillator strengths of quantum transitions and a method of potential profile calculation is developed for the experimentally constructed three-well resonance-tunneling structure — a separate cascade of quantum cascade detector. For the proposed method, a comparison with the results of other methods and with the results of the experiment was carried out. A good agreement between the calculated value of the detected energy and its experimental value has been obtained, the difference being no more than 2.5%. Використовуючи модель ефективної маси для електрона та моделi дiелектричного континууму, отриманi аналiтичнi розв’язки самоузгодженої системи рiвнянь Шредiнгера-Пуассона. Для експериментально створеної триямної резонансно-тунельної структури — каскаду квантового каскадного детектора розроблена квантово-механiчна теорiя електронних стацiонарних станiв, сил осциляторiв квантових переходiв i метод розрахунку її потенцiального профiлю. Для запропонованого методу проведено порiвняння з результатами iнших методiв та результатами експерименту. Отримано добре узгодження мiж розрахованою величиною детектованої енергiї та її експериментальною величиною, якi вiдрiзняються не бiльш, нiж на 2.5%.